Oncological outcomes in fertility-sparing treatment in stage IA-G2 endometrial cancer - Ronsini, Carlo; Mosca, Lavinia; Iavarone, Irene; Nicoletti, Roberta; Vinci, Davide; Carotenuto, Raffaela Maria; Pasanisi, Francesca; Solazzo, Maria Cristina; De Franciscis, Pasquale; Torella, Marco; La Verde, Marco; Colacurci, Nicola; et al. (Frontiers in Oncology, 2022)
Background: The gold standard treatment for early-stage Endometrial Cancer (EC) is hysterectomy with bilateral salpingo-oophorectomy (BSO), with lymphadenectomy. In selected patients desiring pregnancy, fertility-sparing treatment (FST) can be adopted. Our review aims to collect the most incisive studies about the possibility of conservative management for patients with grading 2, stage IA EC. Different approaches can be considered beyond demolition surgery, such as local treatment with Levonorgestrel-release intra-uterine device (LNG-IUD) plus systemic therapy with progestins. Study design: Our systematic review was performed according to the Preferred Reporting Item for Systematic Reviews and Meta-Analysis (PRISMA) statement. PubMed, EMBASE and Scopus databases were consulted, and five studies were chosen based on the following criteria: patients with a histological diagnosis of EC stage IA G2 in reproductive age desiring pregnancy; at least one oncological outcome evaluated. Search imputes were: “endometrial cancer” AND “fertility sparing” AND “oncologic outcomes” AND “G2 or stage IA”. Results: A total of 103 patients were included and treated with a combination of LNG-IUD plus Megestrol Acetate (MA) or Medroxyprogesterone Acetate (MPA); Gonadotrophin-releasing hormone (GnRH) plus MPA/MA; hysteroscopic resectoscope (HR); dilation and curettage (D&C). There is evidence of 70% to 85% complete response after second-round therapy prolongation to 12 months. Conclusions: Conservative measures must be considered temporary to allow pregnancy and subsequently perform specific counseling to adopt surgery. Fertility-sparing management is not the current standard of care for young women with EC. It can be employed for patients with early-stage diseases motivated to maintain reproductive function. Indeed, the results are encouraging, but the sample size must be increased.